2009
DOI: 10.1007/s11192-009-0131-x
|View full text |Cite
|
Sign up to set email alerts
|

Male and female involvement in patenting activity in Spain

Abstract: The involvement of male and female scientists in the technological activity developed in Spain is analysed through the study of patent applications filed with the Spanish OEPM database during the period 1990-2005. Comparative analyses based on participation, contribution and inventors by gender are presented and discussed. The study reveals a low female involvement in technology, which tends to concentrate in specific institutional sectors (public research institutions) and technological sections (A/Human Nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 19 publications
(22 reference statements)
4
22
0
2
Order By: Relevance
“…Second, this study contributes to existing literature on gender-specific collaboration patterns by analyzing gender composition of inventor and designer teams. Studies have thus far shown that women tend to invent in larger patent inventor teams (Mauleón and Bordons 2010;Sugimoto et al 2015;Hoisl and Mariani 2016;Martinez et al 2016;Meng 2018). We extend the analysis of collaboration patterns into design rights and UMs.…”
Section: Introductionmentioning
confidence: 85%
“…Second, this study contributes to existing literature on gender-specific collaboration patterns by analyzing gender composition of inventor and designer teams. Studies have thus far shown that women tend to invent in larger patent inventor teams (Mauleón and Bordons 2010;Sugimoto et al 2015;Hoisl and Mariani 2016;Martinez et al 2016;Meng 2018). We extend the analysis of collaboration patterns into design rights and UMs.…”
Section: Introductionmentioning
confidence: 85%
“…The remaining authors tend to appear in intermediate positions in descending order of their contribution, with senior authors normally listed at the end. However, in some disciplines such as Mathematics, Economics or High Energy Physics, alphabetical order of authors is followed (AMS 2004; Mauleon and Bordons 2007; Engers et al 1999; Birnholtz 2006; Frandsen and Nicolaisen 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Diverse studies, use one of the most important products of technological activity, the patents, as the observation unit (McMillan, 2009;Mauleón & Bordons, 2010). Patents are considered to be good indicators of technological activity (Griliches, 1990;Archibugi, 1992;Basberg, 1987;Nesta & Patel, 2005;Baldini, 2006;OECD, 1997).…”
Section: Review Of the Literature And Question To Be Consideredmentioning
confidence: 99%
“…Other studies based on different aspects of commercial activity, such as advice to companies (Ding et al, 2008) and creation of businesses (Rosa & Dawson, 2006;Dahlstrand & Politis, 2013), also emphasize a lower participation of female researchers. In the case of Spain, we should point out the work of (Mauleón & Bordons, 2010), who studied this topic in Universities and the Spanish National Research Council. The results indicate that only 16% of the patents analysed include a woman amongst its inventors, with a 9% contribution to technological output.…”
Section: Review Of the Literature And Question To Be Consideredmentioning
confidence: 99%